Determinan Pergantian Auditor pada Perusahaan Manufaktur Subsektor Makanan dan Minuman di Bursa Efek Indonesia Tahun 2014-2018 - Ferra Nur Janah; Zulpahmi Zulpahmi; Daram Heriansyah (Diponegoro Journal of Economics, 2021)
This study aimed to determine the effect of Institutional Ownership, Leverage, Financial Distress, Profitability, Company Size, KAP Size, and Board of Commissioners Size on Auditor Switching. The research population is food and beverage sub-sector manufacturing as many as 13 companies. Data analysis and processing techniques used are regretion logistic analysis, the test results show that the variable Institutional Ownership, Leverage, Financial Distress, Profitability, Company Size, and Board of Commissioners Size have a partial effect on the Change of Auditors with a significant value of less than 0.05. While the KAP size has a significant value greater than 0.05, it is stated that there is no significant effect on the Change of Auditors.